Comparing Apples to Oranges: Productivity Convergence and Measurement Across Industries and Countries - Bernard, Andrew B.; Jones, Charles I. (American Economic Review, 1996)
This paper examines the role of sectors in aggregate convergence for 14 OECD countries during 1970-1987. The major finding is that manufacturing shows little evidence of either labor productivity or multifactor productivity convergence, while other sectors, especially services, are driving the aggregate convergence result. To determine the robustness of the convergence results, the paper introduces a new measure of multifactor productivity which avoids many problems inherent to traditional measures of total factor productivity when comparing productivity levels. The lack of convergence in manufacturing is robust to the method of calculating multifactor productivity.